Cooperative effects in vibrated granular systems - Pacheco Martinez, Hector Adrian (2013)
In this thesis we describe experimental studies carried out in three different granular systems. Firstly, we describe the results of experiments and computer simulations carried out to test the validity of a randomly-forced model to describe the behaviour of a vertically vibrated, granular monolayer. We study how a single particle moves across a vibrated roughened surface and show that both a random force and viscous dissipation are needed to match the experimental data. We then simulate a collection of particles driven in this way and compare the structure factor S(k) obtained from simulation with that measured experimentally. The small k behaviour of S(k) reveals a quasi long-range structure which has not been observed previously. Secondly, we study the behaviour of water-immersed granular beds. The first system consisted of spherical barium titanate particles contained in a rectangular cell which is divided into two columns, linked by two connecting holes, one at the top and one at the bottom of the cell. Under vibration the grains spontaneously move into just one of the columns via a gradual transfer of grains through the connecting hole at the base of the cell. We have developed numerical simulations that are able to reproduce this behaviour and provide detailed information on the instability mechanism. We use this knowledge to propose a simple analytical model for this fluid-driven partition instability based on two coupled granular beds vibrated within an incompressible fluid. In the second system to be studied a water-enhanced Brazil nut effect, which occurs when the vibrated granular bed is fully immersed in a liquid, will be describe. We use a bed of glass beads immersed in water and monitor the behaviour of a large steel intruder as the system is vibrated vertically. To aid our understanding, we have developed numerical simulations to model this system and provide detailed information about the fluid and grain motion. The mechanism responsible for the rapid rise of the intruder is shown to be fluid-enhanced ratcheting rather than simple differential drag. Lastly, we describe experiments carried out in a levitation magnet to investigate the behaviour of spheres suspended magnetically in a viscous fluid. Under vibration the spheres attract and for sufficiently large vibration amplitudes the spheres are observed to spontaneously orbit each other. Data collapse shows that the instability occurs at a critical value of the streaming Reynolds number. Simulations are used to provide a detailed understanding of the cause of this instability.